Cardiometabolic multimorbidity and lifetime risk of atrial fibrillation among men and women. (3rd October 2022) - Lu, Z; Ntlapto, N; Tilly, M; Ikram, M A; De Groot, N M S; Kavousi, M
Abstract: Background: Atrial fibrillation (AF) is the most common cardiac arrythmia worldwide, with an increased risk of comorbidity, and significant sex differences in pathophysiology and prognosis. Cardiometabolic disorders, including obesity, hypertension, diabetes mellitus, coronary heart disease, stroke, and heart failure commonly coexist with AF. However, the sex-specific patterns and (combined) impact of cardiometabolic disorders on the risk of new-onset AF remains largely unknown. Purpose: To examine the association between patterns of cardiometabolic multimorbidity and new-onset AF and lifetime risk of AF incidence among men and women. Methods: 4, 113 men and 5, 432 women free of prevalent AF at baseline (from 1996 to 2008) from the Rotterdam Study were included. AF incidents were assessed by electrocardiograms and general practitioners' and hospital records, and followed up to January 1st, 2014. Sex-specific Cox proportional hazards regression models were used to assess the association between the amount of cardiometabolic disorders and risks of new-onset AF. Models were adjusted for traditional cardiovascular risk factors. Remaining lifetime risk for AF was estimated across the cardiometabolic multimorbidity groups at index ages of 55, 65, and ≥75 years up to age 108. Results: Mean age at baseline was 65.5±9.4 years. Median follow-up time was 10.8 years. In the fully-adjusted model, a significant association was found between the amount of cardiometabolic disorders and incident AF among women but not men. Compared to women without cardiometabolic disorders, women with 3 (hazard ratios, 95% conference intervals: 2.17 (1.24–3.79)) and ≥4 comorbidities (4.58 (2.22–9.48)) had higher AF risks. The lifetime risk for AF was significantly increased with the number of cardiometabolic disorders among both men and women. At index age of 55 years, the lifetime risks (95% confidence interval) for AF were 25.2% (17.1–33.4), 24.2% (20.0–28.9), 27.1% (23.2–31.0), 30.0% (24.3–35.7) and 34.1% (22.4–45.7), for 0, 1, 2, 3, and ≥4 comorbid cardiometabolic disorders among men, respectively. Corresponding risks were 16.3% (6.68–25.9), 20.3% (16.3–24.3), 27.6% (24.1–31.2), 23.6% (17.8–29.4) and 33.3% (16.0–50.2) among women. Conclusions: We observed a significant combined impact of cardiometabolic disorders on AF risk, most evidently among women. Participants with cardiometabolic multimorbidity had a significantly increased lifetime risk of AF, especially at a young index age. Funding Acknowledgement: Type of funding sources: None.